Efficient Catalytic Conversion of Ethanol to 1‑Butanol via the Guerbet Reaction over Copper- and Nickel-Doped Porous - Sun, Zhuohua; Couto Vasconcelos, Anaís; Bottari, Giovanni; Stuart, Marc C. A; Bonura, Giuseppe; Cannilla, Catia; Frusteri, Francesco; Barta, Katalin (ACS sustainable chemistry & engineering, 2017)
The direct conversion of ethanol to higher value 1-butanol is a catalytic transformation of great interest in light of the expected wide availability of bioethanol originating from the fermentation of renewable resources. In this contribution we describe several novel compositions of porous metal oxides (PMO) as highly active and selective catalysts for the Guerbet coupling of ethanol to 1-butanol in the temperature range 180–320 °C. The novel PMO catalysts that do not contain any noble metals are obtained by calcination of a series of hydrotalcite precursors synthesized through modular procedures. In particular, catalyst compositions simultaneously containing Cu and Ni dopants have shown excellent catalytic activities. Up to 22% 1-butanol yield at 56% ethanol conversion was reached in a batch mode; recycling and leaching tests showed excellent robustness of the new catalysts. An extensive characterization by means of several techniques such as powder XRD, SEM, TEM, BET, and NH3- and CO2-TPD was performed in order to understand structure–activity trends.